2013
DOI: 10.1080/ac.68.2.2967276
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical diastolic dysfunction in children with Wilson’s disease assessed by tissue Doppler echocardiography: a possible early predictor of cardiac involvement

Abstract: Our study showed results that might be consistent with disease children which probably represents an early stage of cardiac involvem the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…4,21 The study by Arat et al showed that left ventricular wall thickness, left ventricular diameter and left ventricular ejection fraction were similar in both Wilson's patients and the control group. 3 The similar results were published by Elkiran et al and Hlubocka et al 22,23 We suggested that, even though patients in these studies are mostly well treated and had neither severe neurological impairment nor cardiac symptoms, a more comprehensive investigation is needed to evaluate cardiac involvement in a totally asymptomatic patient group. Tissue Doppler echocardiography is a more useful echocardiographic technique to evaluate global and regional myocardial systolic as well as diastolic function when compared to standard echocardiography, particularly for the assessment of asymptomatic patients.…”
Section: Discussionsupporting
confidence: 79%
“…4,21 The study by Arat et al showed that left ventricular wall thickness, left ventricular diameter and left ventricular ejection fraction were similar in both Wilson's patients and the control group. 3 The similar results were published by Elkiran et al and Hlubocka et al 22,23 We suggested that, even though patients in these studies are mostly well treated and had neither severe neurological impairment nor cardiac symptoms, a more comprehensive investigation is needed to evaluate cardiac involvement in a totally asymptomatic patient group. Tissue Doppler echocardiography is a more useful echocardiographic technique to evaluate global and regional myocardial systolic as well as diastolic function when compared to standard echocardiography, particularly for the assessment of asymptomatic patients.…”
Section: Discussionsupporting
confidence: 79%
“…We previously evaluated 22 children with Wilson’s disease with 24-hour ECG monitoring and our study showed that one patient had first-degree atrioventricular block, one had frequent sinus exit block, and four had rare ventricular ectopic beat 8. In our study, all the patients were assessed with ECG before echocardiographic evaluation.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, the use of Doppler echocardiography in children with various diseases has showed the presence of diastolic dysfunction. In particular, tissue Doppler echocardiography has been efficiently performed to establish adverse cardiac effects in the subclinical states . Impaired left ventricular function has been documented in asymptomatic diabetic patients and diastolic dysfunction is the first stage of diabetic cardiomyopathy .…”
Section: Introductionmentioning
confidence: 99%